Shallow epifaunal sea cucumber densities and their relationship with the benthic community in the Okinawa Islands - Kohei Hamamoto; Angelo Poliseno; Taha Soliman; James Davis Reimer (PeerJ, 2022)
Sea cucumbers are important ecological engineers in marine ecosystems. However, the fishery demand of some species, especially large-epifaunal and commercially used (LEC) sea cucumbers, has risen drastically, resulting in serious depletion of local populations for many species. Despite this problem, basic ecological data on sea cucumbers, such as population densities and preferred habitats, are often still insufficient. Here, we report on the population densities of multiple LEC sea cucumber species, and their ambient benthic communities at eight sites around Okinawa Islands. Further, we discuss the correspondence between sea cucumber densities and the surrounding coral communities. Our results show two sites within national or quasi-national parks, Aka and Manza, where stricter rules have been placed on fisheries and land reclamation compared to other areas, had the highest and third highest sea cucumber population densities among sites, respectively. Holothuria atra was observed at all survey sites and made up the majority of sea cucumber populations at all sites except for Chatan and Sesoko, where Holothuria leucospilota and Stichopus chloronotus were most abundant, respectively. Regarding the relationships between benthic composition and LEC sea cucumber species, S. chloronotus was significantly correlated with dead corals, scleractinian corals, and coralline algae. As well, H. leucospilota had significant correlations with rubble. Although there were no significant correlations between any specific scleractinian coral genus and sea cucumber densities, S. chloronotus was marginally insignificant with Platygyra and Psammocora. Notably, medium- to highly valued species were sparse in our surveys, and most of them appeared at only one site. Additionally, at one site (Odo), only three LEC sea cucumber individuals were observed. Combining these facts with relatively low population densities around the Okinawa Islands compared to densities reported in previous research from the Indo-West Pacific Ocean region, we conclude that Okinawan LEC sea cucumber populations have been and are being impacted by high levels of direct (e.g., overexploitation, as well as coastal development) and indirect anthropogenic pressure (e.g., decreasing water quality). To address the current situation, repeated monitoring and more detailed investigations to reveal the drivers that determine LEC sea cucumber species aggregations and population densities are urgently needed, along with more robust management of remaining LEC sea cucumber populations.